Hafnium Chloride, an Alternative Staining Reagent for Biological Electron Microscopy - Baranyi, Magdalena Victoria (Jihočeská univerzita, 2021)
This study focuses on the staining pattern of the non-radioactive heavy metal EM stain HfCl4, used during freeze substitution specimen preparation. HfCl4 was investigated as an alternative for the prominent uranyl acetate, since uranium based materials have been placed under heavy restrictions and bans worldwide. We have found a strong HfCl4 staining pattern of microtubules in myoepithelial cells of Ixodes ricinus salivary glands. Additionally, in several samples, HfCl4 was found to completely fill the cytoplasm of the myoepithelial cells. Nonetheless, artefact formation around granulated cells was also experienced.
Hafnium Chloride, an Alternative Staining Reagent for Biological Electron Microscopy
Keywords: electron microscopy; transmission electron microscopy; fixation; staining; uranyl acetate; hafnium chloride; radioactive; ixodes ricinus; salivary glands; imaging; microtubules; myoepithelial cell; cytoplasm; electron microscopy; transmission electron microscopy; fixation; staining; uranyl acetate; hafnium chloride; radioactive; ixodes ricinus; salivary glands; imaging; microtubules; myoepithelial cell; cytoplasm